2006
DOI: 10.1007/11733836_22
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Similarity Join on Uncertain Data

Abstract: Abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
78
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 27 publications
0
78
0
Order By: Relevance
“…It is extensively studied in [4], [11], [14]. Note that all instances in a multi-valued object exist simultaneously instead of mutually exclusive in an uncertain object.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It is extensively studied in [4], [11], [14]. Note that all instances in a multi-valued object exist simultaneously instead of mutually exclusive in an uncertain object.…”
Section: Related Workmentioning
confidence: 99%
“…The existing model for handling similarity joins over objects with multiple instances follows the probabilistic semantics on uncertain objects [4], [11], [14] and aims to capture relative instance distribution among objects with multiple instances. Nevertheless, uncertain objects are inherently different than multi-valued objects.…”
Section: Introductionmentioning
confidence: 99%
“…A number of problems in querying uncertain data have also been studied, such as indexing [41], similarity join [26], nearest neighbor query [27], skyline query [34], clustering [28,30], etc. Top-k Query Processing over Uncertain Data.…”
Section: Related Workmentioning
confidence: 99%
“…Uncertainty is inherent in such applications due to various factors such as data randomness and incompleteness, limitation of equipment, and delay or loss in data transfer. A number of issues have been recently addressed; these include modeling uncertainty [2,36], query evaluation [10,13,14,37], indexing [11,41], top-k queries [22,35,39,42], skyline queries [34], joins [26,27], nearest neighbor query [5,9,27], clustering [28,30], etc.…”
Section: Introductionmentioning
confidence: 99%
“…A number of problems in querying uncertain data have also been studied, such as indexing [18], similarity join [5], nearest neighbor query [9], skyline query [15], clustering [10], etc. Relatively complete and detailed study of existing techniques on managing uncertainty can be found in [14] and [20].…”
Section: Related Workmentioning
confidence: 99%